Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.visres.2016.12.014
|View full text |Cite
|
Sign up to set email alerts
|

General and specific factors in the processing of faces

Abstract: The ability to recognize faces varies considerably between individuals, but does performance co-vary for tests of different aspects of face processing? For 397 participants (of whom the majority were university students) we obtained scores on the Mooney Face Test, Glasgow Face Matching Test (GFMT), Cambridge Face Memory Test (CFMT) and Composite Face Test. Overall performance was significantly correlated for each pair of tests, and we suggest the term f for the factor underlying this pattern of positive correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

24
98
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(123 citation statements)
references
References 56 publications
24
98
0
Order By: Relevance
“…Rather, the bottom line of this research is that there is not a single common factor that reliably explains a substantial portion of the effects of priors on perception. Therefore, this study is in line with previous research that has reported low pairwise correlations between visual tasks and found either no common factors in visual perception (Cappe et al 2014; Goodbourn et al 2012; Grzeczkowski et al 2017) or only few minor sub-factors of perception specific to a single task or narrow processing mechanism (Bosten et al 2017;Verhallen et al 2017;Ward et al 2016). Likewise, the present study adds weight to arguments about the principal difficulty of establishing general prior-including models of optimal perceptual behaviour that could be applied to different tasks (Rahnev & Denison, 2018).…”
Section: Priors Affect Perception In a Variety Of Wayssupporting
confidence: 92%
“…Rather, the bottom line of this research is that there is not a single common factor that reliably explains a substantial portion of the effects of priors on perception. Therefore, this study is in line with previous research that has reported low pairwise correlations between visual tasks and found either no common factors in visual perception (Cappe et al 2014; Goodbourn et al 2012; Grzeczkowski et al 2017) or only few minor sub-factors of perception specific to a single task or narrow processing mechanism (Bosten et al 2017;Verhallen et al 2017;Ward et al 2016). Likewise, the present study adds weight to arguments about the principal difficulty of establishing general prior-including models of optimal perceptual behaviour that could be applied to different tasks (Rahnev & Denison, 2018).…”
Section: Priors Affect Perception In a Variety Of Wayssupporting
confidence: 92%
“…Rather, the bottom line of this research is that there is not a single common factor that reliably explains a substantial portion of the effects of priors on perception. Therefore, this study is in line with previous research that has reported low pairwise correlations between visual tasks and found either no common factors in visual perception (Cappe et al 2014; Goodbourn et al 2012;Grzeczkowski et al 2017) or only few minor sub-factors of perception specific to a single task or narrow processing mechanism Verhallen et al 2017;Ward et al 2016). Likewise, the present study adds weight to arguments about the principal difficulty of establishing general prior-including models of optimal perceptual behaviour that could be applied to different tasks (Rahnev & Denison, 2018).…”
Section: Priors Affect Perception In a Variety Of Wayssupporting
confidence: 92%
“…This is evidenced by the heterogeneous patterns of performance across tests in studies of SRs described above (see Table ) and also by studies of individual differences in face processing more broadly. The proportion of shared variance ( r 2 ) between face processing tasks is typically in the range of .10 to .25 and appears to depend on the type of subprocess involved in performing tasks (e.g., Bate et al ., ; Burton, White, & McNeill, ; Fysh, ; McCaffery, Robertson, Young, & Burton, ; Verhallen et al ., ). When considering other abilities that may predict performance in real‐world tasks such as CCTV review and surveillance, this problem is more acute.…”
Section: Introductionmentioning
confidence: 97%